GRAIN YIELD OF CORN HYBRIDS AS AFFECTED BY PLANT DENSITY IN TWO MANAGEMENT LEVELS OF WATER AND SOIL FERTILITY - PEIXOTO, CLAUDIO DE MIRANDA (1997)
The changes in plant traits observed in the most recent com cultivars determine the need of reviewing the recommendation of management practices. With the objective to evaluate the response of three com hybrids (Cargill 901, Pioneer 3063 e Pioneer 3207) to four plant densities (30, 50, 70 e 90 000 pilha), in two management level, two experiments were conducted at Rio Pardo-RS, Brazil, in the 1994/95 growing season. The experiment with high level of management received supplementary irrigation and a higher level of fertilization than the experiment with medium level of management. In both trials, there were differences among hybrids in their response to plant population. In the trial with high management level, plant populations that gave maximum grain yields were higher than that with medium management levei. The hybrids evaluated presented low increase in the percent of barren planto and low reduction in the ear number per plant as plant density was increased, in the two management level.